Microstructure and microhardness properties of Fe-Cr-Al2O3 composites - Saidatulakmar, Shamsuddin; Shamsul Baharin, Jamaludin, Prof. Dr.; Zuhailawati, H.; Zainal Arifin, A. (Universiti Putra Malaysia (UPM), 2011)
Link to publisher's homepage at www.upm.edu.my/